Creación de un reportaje periodístico sobre planned parenhood, año 2022 - Chuncho Caminos, Melissa Xiomara (Machala, 2022)
Social problems encompass many issues addressed by society, some of which extend to a wider and global audience, and are therefore covered by different media in their public agendas and reported through their journalistic channels and formats. The United States has been a pioneer in different areas such as innovation, communication and social, so the issues that arise there reach other countries and have relevance in the same, being a topic that is talked about and generates opinions and / or new needs. About this context, one of the major issues that arose in this country, arose in 2015 and it was with the non-governmental organization, Planned Parenthood. Its repercussion was reflected on the issue of abortion, when it was persecuted for the denunciation of trafficking in tissues or organs of aborted fetuses, a situation that became known by the dissemination of videos in which conversations between the executives of the entity and some alleged buyers, who made the complaint and were part of a pro-life collective, stand out. This paper focuses on the creation of a report with the theme "Planned Parenthood, a questioned organization". For this purpose, a bibliographic research on the journalistic genre of the report was carried out. In addition, the details of the Planned Parenthood case were investigated: bibliographic research, observation and interviews to different gynecology and obstetrics professionals. The report was published in a Machala media, called Info Orense.
Los problemas sociales engloban muchas temáticas abordadas por la sociedad, algunas de las mismas se extienden a un público más amplio y global, por ello son cubiertas por diferentes medios de comunicación en sus agendas públicas e informadas por sus canales y formatos periodísticos. Estados Unidos ha sido pionero en diferentes áreas como innovación, comunicación y social, por lo que los temas que surgen allí llegan a otros países y tienen relevancia en la misma, al ser un tema del que se habla y genera opiniones y/o necesidades nuevas. Sobre este contexto, una de las grandes problemáticas que surgieron en este país, surgió en el año 2015 y fue con la organización no gubernamental, Planned Parenthood. Su repercusión se reflejó sobre el tema del aborto, al ser perseguida por la denuncia de traficar con tejidos u órganos de fetos abortados, situación que se dio a conocer por la difusión de videos en el que sobresalen conversaciones entre los ejecutivos de la entidad y unos supuestos compradores, quienes hacían la denuncia y formaban parte de un colectivo pro-vida. El presente trabajo se enfoca en la creación de un reportaje con el tema “Planned Parenthood, una organización cuestionada”. Para ello, se hizo una investigación bibliográfica sobre el género periodístico del reportaje. Además se indagó sobre los detalles del caso de Planned Parenthood: investigación bibliográfica, observación y entrevistas a distintos profesionales de ginecología y obstetricia . El reportaje fue publicado en un medio de Machala, denominado Info Orense.
Keywords: REPORTAJE; PROPUESTA PERIODISTICA; PLANNED PARENTHOOD; CONTENIDO; PROBLEMA SOCIAL